Mental disorders and earnings: results from the Nigerian National Survey of Mental Health and Well-Being (NSMHW) (2012)
Background: Mental disorders are associated with a loss in earnings both at the individual and societal level. Very few studies have addressed the issue of the cost of mental illness in Sub-Saharan Africa. These studies have been largely hospital based, localized, and have addressed only a few mental disorders using very small sample sizes. Aims of the Study: To examine the impact of mental disorders on earnings of affected persons. Methods: Mental disorders on and personal earnings were assessed in a representative sample of 1,889 Nigerians aged 18-64 years in an epidemiological survey. Version 3.0 of the World Health Organization Composite International Diagnostic Interview (WHO CIDI) was used to assess mental disorders. Respondents were also asked to report their personal earnings before tax in the past 12 months, while authors predicted personal earnings in the same period from information about 12 month and life time DSM IV mental disorders among respondents. Results: A 12-month prevalence of Serious Mental Illness (SMI) was found in 0.5% of the sample while other 12-month disorders had a prevalence of 4.83%. The prevalence of other lifetime disorders was 4.14%. The mean annual impact of serious mental illness was 60,126 Naira (US$ 463). At the level of the society the annual impact was 21.6 billion Naira (US$ 166.2 million). Discussion: Mental disorders have an enormous individual and societal financial burden. This impact appears more severe in males. Implications for Health Care Provision and Use: Mental disorders have enormous negative impacts on earnings both at the individual and societal level. This analysis highlights the financial value of lost earnings in the absence of such disorders. Implications for Health Policies: An increase in spending on mental health based on proportionate economic burden of mental disorders may substantially reduce financial losses due to mental disorders. Implications for Further Research: In the present study, only the indirect health care costs have been assessed. Future research should consider direct costs.